FRI0200 Achievement of low disease activity (LDA) at 3 months predicts clinical remission (REM) at 1 year of infliximab (IFX) therapy in ra: post-hoc analysis of a randomized double-blind clinical study (rising study). (23rd January 2014) - Takeuchi, T.; Yano, T.; Inui, T.; Yoshinari, T.; Miyasaka, N.; Abe, T.; Koike, T.
Abstract : Background: In treatment of RA using TNF-inhibitors, switching to another treatment is recommended if a patient shows moderate or high disease activity (MDA, HDA) at 3 months (1 ) . Meanwhile, dose-escalation of IFX was performed for patients with inadequate response to standard-dose treatment in clinical practice. Therefore, predicting the long-term efficacy of both standard and higher-dose of IFX therapy at 3 months is seemed to be extremely important. Objectives: The RISING study is a randomized double-blind clinical study of IFX therapy in MTX-refractory RA (2 ) . Using data obtained in this study, we conducted post-hoc analysis to determine the probability of achieving REM or LDA at week 54 (w54) based on the disease activity at week 14 (w14) by using logistic regression analysis. Methods: In the RISING study, after patients received 3 mg/kg IFX infusion at weeks 0, 2, and 6, they were randomly assigned to three groups: 3, 6, or 10 mg/kg IFX, every 8 weeks from w14 to w46 in a double- blind manner (n=307). Disease activities (SDAI, DAS28-CRP) were evaluated at w14 and w54. Results: In each treatment group, disease activity at w14 closely correlated with that at w54 (p<0.0001). In the logistic regression analysis, median effective level (95%CI) of SDAI at w14 for attaining SDAI-REM at w54 in 3, 6, and 10 mg/kg groups were 4.4 (-1.1–7.0), 8.0 (4.4–11), and 7.9 (2.0–11), and those for attaining SDAI-LDA were 18 (13–24), 22 (17–28), and 28 (22–41), respectively (Figure ). These results may show that patients who did not achieve SDAI-LDA at w14 had less than 50% probability to attain SDAI-REM at w54 even in higher-dose groups. In addition, achieving at least SDAI-MDA at w14 seemed to be necessary to have high probability of attaining SDAI-LDA at w54 in 3 and 6 mg/kg groups. In contrast, high probability to attain SDAI-LDA at w54 was observed in patients with "close to SDAI-HDA" at w14 in 10 mg/kg group. The analysis using DAS28-CRP showed similar results. Image/graph: Conclusions: In IFX treatment for RA, the probability of attaining REM or LDA at 1 year can be predicted from the disease activity at w14 in 3 mg/kg group as well as in 6 or 10 mg/kg group. These results may provide a useful index of IFX treatment strategy (including dose-escalation) to attain REM or LDA; the goal of RA treatment. References: Singh JA, et al. Arthritis Care Res 2012;64:625. Takeuchi T, et al. Mod Rheumatol 2009;19:478. Disclosure of Interest : T. Takeuchi Speakers bureau: Abbott Japan, Bristol-Myers Squibb, Chugai Pharmaceutical, Eisai, Janssen Pharmaceutical, Mitsubishi Tanabe Pharma, Novartis, Pfizer Japan, Takeda Pharmaceutical, T. Yano Employee of: Mitsubishi Tanabe Pharma, T. Inui Employee of: Mitsubishi Tanabe Pharma, T. Yoshinari Employee of: Mitsubishi Tanabe Pharma, N. Miyasaka Grant/research support from: Abbott Japan, Astellas Pharma, Chugai Pharmaceutical, Daiichi Sankyo, Mitsubishi Tanabe Pharma, Takeda Pharmaceutical, Speakers bureau: Benesis, Otsuka Pharmaceutical, T. Abe: None Declared, T. Koike Speakers bureau: Abbott Japan, Bristol-Myers Squibb, Chugai Pharmaceutical, Eisai, Mitsubishi Tanabe Pharma, Otsuka Pharmaceutical, Pfizer, Takeda Pharmaceutical